Enhancing the Cancer Patients' Resilience and Motivation via the Nurse Educator Model Intervention - Yulia, Sri; Muliyadi, Muliyadi (Journal of Educational, Health and Community Psychology, 2024)
Cancer patients need health education as one of the important nursing interventions for adaptation to the deterioration in physical and psychological conditions associated with their quality of life. A quasi-experiment study with a post-test with a control group design has been conducted aiming to test the effectiveness of the Nurse Educator Model (NEM) on the motivation and resilience of cancer patients. A total of 38 people in the intervention group and 40 people in the control group of stage III and IV cancer patients from five chemotherapy units were involved. Motivation and resilience were measured using questionnaires and data were analyzed by independent t-test. The results showed a significant effect of NEM intervention on patient motivation and no significant effect on the resilience of cancer patients. Nurses need to ensure consistent application of NEM to increase cancer patients' motivation and consider other things that affect cancer patients' resilience.